Diagnostic Ultrasound Detection of Changes in Femoral Muscle Mass Recovery after Tibial Plateau Levelling Osteotomy in Dogs - Frank, Ilan; Duerr, Felix; Zanghi, Brian; Middleton, Rondo; Lang, Linda (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The goal of this study was to develop a clinically feasible ultrasound (US) protocol that can detect changes in thigh muscle mass in dogs after stifle surgery. The primary aim of this study was to compare previously described US measurement locations of the canine thigh for detecting changes in muscle mass in dogs recovering from tibial plateau levelling osteotomy (TPLO).Study Design This was a prospective, exploratory pilot study. Adult dogs (n = 7) undergoing pet-owner elected TPLO were enrolled. Twelve different US measurements were performed in triplicate by a single experienced observer. Measurements were performed at 0, 2, 4 and 8 weeks after surgery at a proximal and distal location along the femur. Data from all available time points and locations were analysed for the main effect of time within modalities.Results A total of 1,008 US measurements were performed. Measurements of the transverse sectional area of the rectus femoris muscle detected significant (p  ≤  0.05) muscle loss between weeks 0 and 2 at the lateral and medial aspects of the distal location (19% and 15% respectively). Measurements of the thigh muscle thickness were significantly (p < 0.01) increased between 2nd- and 8th- week time points at the lateral aspect of the proximal location (26%).Conclusion The proximal femoral location, measured from the lateral aspect, appears to be the most suitable US measurement for detecting increases in femoral muscle mass in dogs recovering from TPLO. The provided pilot data suggest that further research evaluating this outcome measure is indicated.
Keywords: thigh circumference; ultrasound; muscle recovery; tibial plateau levelling osteotomy; dogs